Targeting lipophagy and nuclear receptors in metabolic-associated fatty liver disease: insights from traditional Chinese medicine - Yue, Ting; Huang, Nafei; Zhao, Ziming; Yu, Lili; He, Xiaoming; Yu, Xiao; Zheng, Yi (Frontiers in Pharmacology, 2026)
Background: Metabolic associated fatty liver disease (MAFLD) represents a globally prevalent chronic hepatic disorder hallmarked by excessive lipid accumulation within hepatocytes. This condition can progressively deteriorate to cirrhosis and hepatocellular carcinoma, thereby imposing a substantial healthcare burden. Numerous laboratory studies confirm that drugs targeting the nuclear receptor (NR)-lipophagy axis exhibit preventive and therapeutic potential for MAFLD. However, most remain confined to animal and cell models, and no specific MAFLD therapies are clinically available. In contrast, traditional Chinese medicine (TCM) has garnered considerable interest due to its unique theoretical framework and clinical efficacy in MAFLD management. Purpose: This article systematically reviews existing herbal compounds, extracts, and active metabolites that target the NR-lipophagy interaction for MAFLD treatment. It aims to facilitate the development of low-side-effect herbal formulations and offer valuable insights for future research on the NR-lipophagy axis. Method: Search terms including “MAFLD”, “nuclear receptor”, “lipophagy”, “Compound Traditional Chinese Medicine”, “active metabolites”, “natural products”, and “disease” were combined for literature retrieval. Result: As modulators of pleiotropic NRs, certain herbal metabolites mimic endogenous ligands to exert regulatory lipolysis effects—synergistically modulating lipid metabolism, mitigating oxidative stress, and suppressing inflammation during MAFLD intervention. Herbal compound preparations modulate the NR-lipophagy axis via multi-target, multi-pathway mechanisms: moderately activating fatty acid (FA) oxidation pathways while repressing lipogenesis, thereby achieving sustained amelioration of MAFLD. Conclusion: TCM (including herbal compound preparations, extracts, and active metabolites) exerts therapeutic effects on MAFLD by inducing lipophagy through diverse pharmacological mechanisms and NR-associated signaling pathways. These agents emerge as promising focal points for MAFLD basic research and potential candidates for MAFLD drug development, offering reduced side effects and enhanced therapeutic efficacy.